2021
DOI: 10.1021/acs.est.1c01723
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Rich Hierarchical Porous UiO-66(Zr) for Tunable Phosphate Removal

Abstract: The introduction of defects into hierarchical porous metal−organic frameworks (HP-MOFs) is of vital significance to boost their adsorption performance. Herein, an advanced template-assisted strategy has been developed to fine-tune the phosphate adsorption performance of HP-MOFs by dictating the type and number of defects in HP-UiO-66(Zr). To achieve this, monocarboxylic acids of varying chain lengths have been employed as template molecules to fabricate an array of defect-rich HP-UiO-66(Zr) derivatives followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 48 publications
0
76
0
Order By: Relevance
“…Many studies show that Zr and Ce have an affinity to phosphate, having efficiency adsorption capacity towards phosphate. 48,49 The characterization results above also suggested that phosphate can be attached to MOF-808(Zr/Ce). Therefore, the adsorption properties of MOF-808(Zr/Ce) for phosphate were also investigated.…”
Section: Adsorption Of Phosphatementioning
confidence: 86%
“…Many studies show that Zr and Ce have an affinity to phosphate, having efficiency adsorption capacity towards phosphate. 48,49 The characterization results above also suggested that phosphate can be attached to MOF-808(Zr/Ce). Therefore, the adsorption properties of MOF-808(Zr/Ce) for phosphate were also investigated.…”
Section: Adsorption Of Phosphatementioning
confidence: 86%
“…Different structures of UIO-66 have differ-ent functions. Therefore, controllable preparation of UIO-66 according to its different functions and properties of different spatial structures is a method to utilize UIO-66 complexes [14] effectively. UIO-66 is generally prepared by accurately weighing 0.053 g of ZrCl 4 (0.227 mmol) into 24.9 g of DMF (340 mmol) solvent and sonicated to dissolve completely.…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…A more recent concept, defect engineering, has gained great interest in MOFs to expose active sites hidden in the frameworks and to expand their potential applications. A heedful removal of part of the linkers or metal nodes, commonly employed in the defect engineering, produces a great diversity in MOF features including larger accessible internal area, enhanced porosity, and increased number of catalytic and adsorption sites, which significantly improve the performances in relevant applications. , For example, defective UiO-66 dramatically increased the catalytic performances by the addition of trifluoroacetic acid, which caused the missing linker defect in the framework . UiO-66 is a prototype MOF in defect engineering and it easily tolerates a great number of defects without loss of the structural framework due to the strong metal-linker coordination and high connectivity of the framework, which makes it fascinating and unique in the MOF family .…”
Section: Introductionmentioning
confidence: 99%